2020
DOI: 10.1016/j.jelectrocard.2020.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Wide complex tachycardia in a COVID-19 patient: What is the mechanism?

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
(2 reference statements)
0
5
1
Order By: Relevance
“…In some studies, STEMI has been reported in some COVID-19 patients. 16 In our study, STEMI was detected in 4.8% of the patients with COVID-19 while it was not observed in any of the patients in the control group. Since there was no significant difference between the two groups, it can be concluded that ST-segment elevation is not a characteristic ECG finding for COVID-19.…”
Section: Discussioncontrasting
confidence: 46%
“…In some studies, STEMI has been reported in some COVID-19 patients. 16 In our study, STEMI was detected in 4.8% of the patients with COVID-19 while it was not observed in any of the patients in the control group. Since there was no significant difference between the two groups, it can be concluded that ST-segment elevation is not a characteristic ECG finding for COVID-19.…”
Section: Discussioncontrasting
confidence: 46%
“…A case of a transient complete heart block in a 54-year-old man with critical COVID-19 was recently reported [ 14 ]. Atrial tachycardia or atypical atrial flutter with 2:1 conduction and a concomitant wide QRS morphology in a COVID-19 positive patient was also reported [ 15 ].…”
Section: Covid-19 and Markers Of Myocardial Damagementioning
confidence: 99%
“…In SVT with LBBB morphology due to aberrant conduction, the QRS complex in lead V1 exhibits a narrow (<30 msec) initial R wave and a sharp, smooth descent (Figure 5A ). 28 Notching in the downslope of the S wave in lead V1 and/or V2 and an interval from the onset of the QRS complex to the nadir of the S wave >60 mseconds suggests a diagnosis of VT (Figure 5B ), an observation initially made by Josephson, et al 29 , 30 These findings are more likely to be observed in patients with previous anterior wall infarction.…”
Section: Electrocardiographic Featuresmentioning
confidence: 78%